A computational tool that supports formal diagnosis of process design - Ramos, P.; Fiadeiro, J. L. (Information and Software Technology, 1998)
Computational tools that support process design have been used widely in organisation. These tools usually provide methods and notations (formal or diagrammatic) that are used to describe and simulate the behaviour of processes, and validate them with the users. The validation procedure supports mainly syntax validation and consistency analysis against organisation constraints (structure, tasks, documents, etc.). No further analysis is made with regard to the compliance of a process design with respect to organisational requirements. In this paper we present a software tool which detects designs that do not accomplish prerequisites supplied by the organisation. The software tool is supported by formal techniques from artificial intelligence and computer science.